Dispersion of Carbon Nanotubes with Different Types of Superplasticizer as a Dispersing Agent for Self-Sensing Cementitious Materials - Pedro de Almeida Carísio; Yasmim Gabriela dos Santos Mendonça; Carlos Fernando Teodósio Soares; Oscar Aurelio Mendoza Reales; Eduardo de Moraes Rego Fairbairn; Romildo Dias Toledo Filho (Applied Sciences, 2021)
Due to their exceptional electrical properties, carbon nanotubes (CNTs) can be applied as conductive fillers to develop self-sensing cement-based matrices. In order to obtain an adequate self-sensing response, CNTs must be evenly dispersed through the cement matrix in a volume sufficient enough to create an electric percolation network. This is challenged by the difficulty of dispersing CNTs; therefore, there is a demand for an efficient dispersing agent that can be filled by superplasticiezers, which are products of known compatibility with cement and high availability. This research explores the use of four commercial superplasticizers available in Brazil, both naphthalene and ether polycarboxylate-based, as dispersing agents for CNTs in water. Ultrasonic energy was applied to aqueous solutions containing CNTs and superplasticizers. UV–Vis spectroscopy and ξ-potential measurements were used to investigate which superplasticizer was more effective to disperse the CNTs. Cement pastes were produced with the CNT dispersions and their electrical resistivity was measured. It was found that only superplasticizers without aliphatic groups in their structure were capable of dispersing CNTs in water. It was concluded that second-generation naphthalene-based superplasticizers were more efficient dispersing agents for CNTs than third-generation ether polycarboxylate-based ones for self-sensing applications.